2014
DOI: 10.4031/mtsj.48.5.8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Turbulent Dissipation Rates Beneath an Antarctic Ice Shelf

Abstract: A B S T R A C TMicrostructure shear, temperature, and conductivity observations from a tethered profiler have been made beneath George VI Ice Shelf to examine processes driving vertical heat flux in the oceanic turbulent boundary layer. Such measurements at the ice-ocean interface within the cavity of an ice shelf are unprecedented, requiring the deployment of a profiler through 400-m deep access boreholes. We describe the drilling technique developed for this purpose, which involves using a brush to widen the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 13 publications
4
15
0
Order By: Relevance
“…In line with the increasing energy levels as a function of mean flow speed, the rate of TKE dissipation increases from a minimum of ~10 ‐9 W/kg at both MAVS to a maximum of ~10 ‐6 W/kg at the upper MAVS and ~10 ‐7 W/kg at the lower MAVS (Figures a and b). The rate of TKE dissipation is similar to that observed under sea ice in the Arctic (McPhee, ; Peterson et al, ) and the Antarctic (McPhee, ; McPhee & Martinson, ), but is greater than that observed beneath Pine Island Ice Shelf (~10 ‐9 W/kg; Kimura et al, ) and George VI Ice Shelf (~10 ‐10 W/kg; Venables et al, ). As a function of mean flow speed, ε scales as a power law at the upper MAVS ( r 2 = 0.93) and exponentially at the lower MAVS ( r 2 = 0.93).…”
Section: Resultssupporting
confidence: 72%
“…In line with the increasing energy levels as a function of mean flow speed, the rate of TKE dissipation increases from a minimum of ~10 ‐9 W/kg at both MAVS to a maximum of ~10 ‐6 W/kg at the upper MAVS and ~10 ‐7 W/kg at the lower MAVS (Figures a and b). The rate of TKE dissipation is similar to that observed under sea ice in the Arctic (McPhee, ; Peterson et al, ) and the Antarctic (McPhee, ; McPhee & Martinson, ), but is greater than that observed beneath Pine Island Ice Shelf (~10 ‐9 W/kg; Kimura et al, ) and George VI Ice Shelf (~10 ‐10 W/kg; Venables et al, ). As a function of mean flow speed, ε scales as a power law at the upper MAVS ( r 2 = 0.93) and exponentially at the lower MAVS ( r 2 = 0.93).…”
Section: Resultssupporting
confidence: 72%
“…The primary contribution of tides to the thermodynamic exchange processes described in section 7.2.1 is through increased turbulence (represented by u* ) in the ocean layer adjacent to the ice base. Direct measurements of turbulence under ice shelves are rare (Kimura et al, ; Stanton et al, ; Venables et al, ). In models, u* can be approximated from the velocity magnitude | u s | of the model layer nearest the ice base as u* = C D 1/2 | u s |, where C D is a nondimensional quadratic drag coefficient that is frequently taken to be between 0.002 and 0.003.…”
Section: Effect Of Tides On Ice Shelf Basal Mass Balancementioning
confidence: 99%
“…Although the observations from George IV Ice Shelf reported by Kimura et al (2015) showed clear evidence for double-diffusive convection, Venables et al (2014) noted that some turbulent shear profiles taken beneath George VI Ice Shelf showed low dissipation values concurrent with double-diffusive staircases, while others showed no staircases and high dissipation values. One hypothesis is that double-diffusive convection is suppressed when turbulence exceeds a critical threshold.…”
Section: Introductionmentioning
confidence: 82%
“…Certain observations cannot be explained by the damping effect of stratification. Borehole observations made on the George VI Ice Shelf (Venables et al 2014;Kimura et al 2015), found layers (or 'thermohaline staircases') in the temperature and salinity profiles adjacent to the ice. Although layers can form in fluids with a single stratifying component (Phillips 1972), Kimura et al (2015) argued that the staircases observed beneath George VI Ice Shelf are associated with the difference between the molecular diffusivities of temperature and salinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation